2016
DOI: 10.1101/047209
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An evolutionary medicine perspective on Neandertal extinction

Abstract: The Eurasian sympatry of Neandertals and anatomically modern humans -beginning at least 45,000 years ago and lasting for more than 5,000 years -has long sparked anthropological interest into the factors that potentially contributed to Neandertal extinction. Among many different hypotheses, the "differential pathogen resistance" extinction model posits that Neandertals were disproportionately affected by exposure to novel infectious diseases that were transmitted during the period of spatiotemporal sympatry wit… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 81 publications
(96 reference statements)
3
4
0
Order By: Relevance
“…Our results are consistent with previous studies that have reported lower genetic diversity in archaic humans than in present-day humans, both genome-wide and in protein-coding regions (Castellano et al 2014;Meyer et al 2012;Prufer et al 2017;Prufer et al 2014). In a recent study, lower protein-coding diversity observed in a set of 73 innate immunity genes (Sullivan et al 2017) was interpreted as suggesting that Neandertals may have lacked the functional immune diversity necessary to survive new pathogen infections (Houldcroft and Underdown 2016;Sullivan et al 2017;Wolff and Greenwood 2010). Here, we re-evaluated this hypothesis by studying the diversity of a set of 1,548 innate immune genes, and by explicitly comparing them to all autosomal protein-coding genes.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our results are consistent with previous studies that have reported lower genetic diversity in archaic humans than in present-day humans, both genome-wide and in protein-coding regions (Castellano et al 2014;Meyer et al 2012;Prufer et al 2017;Prufer et al 2014). In a recent study, lower protein-coding diversity observed in a set of 73 innate immunity genes (Sullivan et al 2017) was interpreted as suggesting that Neandertals may have lacked the functional immune diversity necessary to survive new pathogen infections (Houldcroft and Underdown 2016;Sullivan et al 2017;Wolff and Greenwood 2010). Here, we re-evaluated this hypothesis by studying the diversity of a set of 1,548 innate immune genes, and by explicitly comparing them to all autosomal protein-coding genes.…”
Section: Discussionsupporting
confidence: 93%
“…It has been suggested that lack of functional variation in immune-related genesespecially in genes related to the innate immune system which is known to serve as a first defence mechanism against pathogen detection -, some of which are targets of long-term balancing selection (Bitarello et al 2018;Key et al 2014b;Meyer and Thomson 2001), could have contributed to Neandertal extinction (Houldcroft and Underdown 2016;Sullivan et al 2017;Wolff and Greenwood 2010). This is known as the differential pathogen resistance hypothesis (DPRH), and (Sullivan et al 2017) recently presented evidence both for and against this hypothesis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, OAS1 is among the most diverse genes in both humans and non-human primates. Indeed, a recent analysis of genome-wide sequence data from a total of 55 individuals from four non-human ape species, chimpanzee (Pan troglodytes ellioti), bonobo (Pan paniscus), gorilla (Gorilla gorilla gorilla), and orangutan (Pongo abelii), identified OAS1 as in the top 1% of genes showing the largest levels of nucleotide diversity among ape species [43], consistent with a scenario of long-term balancing selection (OAS2 and OAS3 are ranked in the 60th and 36th percentile of the genome-wide distribution, respectively) or, as previous research has suggested, rapid evolution across the primate order [44]. Further supporting the idea of balancing selection on the introgressed haplotype, our functional data suggest that the Neandertal haplotype contributes a range of gene expression responses in a cell-type and stimulusspecific manner.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of surgical interventions, plants with analgesic properties may also have been used. Sullivan et al suggested that novel pathogens and differential pathogenetic resistance may have contributed to the extinction of Neanderthals. A recent example of the devastating effects that pathogens can have was the decimation of the indigenous people of the American continent, where around 90% of the population died from a range of infectious diseases against which they had no natural resistance.…”
Section: Discussionmentioning
confidence: 99%